COUNTER-TERRORISM COOPERATION IN THE ASEAN REGIONAL FORUM (ARF) FROM THE PERSPECTIVE OF INDONESIA DEFENSE DIPLOMACY - Wilujeng, Nila Febri; Swastanto, Yoedhi; Joostensz, Thomas Gabriel (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2021)
Terrorism is a threat that not only jeopardizes a country's security, but also the survival of ASEAN as a regional organization, the security of peace and stability, and the region's overall economic possibilities. This research aimed to examine the implementation of Counter-terrorism (CT) cooperation in the ASEAN Regional Forum (ARF) from the perspective of Indonesia's defense diplomacy. The research method used was the qualitative method which is based on the combination of interviews and literature review regarding ASEAN’s or ARF’s Counter-terrorism cooperation and Indonesia’s defense diplomacy from the year 2015-2019. The findings showed that CT cooperation is less discussed in the mechanism of the ARF since the current focus of ARF is on Trafficking in Person (TIP) and threats of Chemical, Biological, Radiological, and Nuclear (CBRN). Meanwhile, from the perspective of defense diplomacy, Indonesia has successfully initiated ARF Statement on Preventing and Countering Terrorism and Violent Extremism Conducive to Terrorism (VECT) with Australia and New Zealand in 2019. However, it is undeniable that CT cooperation through the ARF mechanism remains difficult to achieve due to several obstacles, including the differences of national interests and legal framework, the principle of non-interference, and the existence of mutual distrust between participating countries.